Lippincott's essentials for nursing assistants : a humanistic approach to caregiving - Carter, Pamela J. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
Provides the foundational concepts and facts that a nursing assistant needs to function competently in the workplace, be it a long-term care facility, an acute care facility, or a home health agency